Qualitative Analysis of Taxpayers’ Lived Experience of Tax Justice in Iran: An Approach Based on In-Depth Interviews - Akbari, Mohammad Javad; Ahmadi, Faegh; Valinia, Seyyed Nima (Business, Marketing, and Finance Open, 2026)
The purpose of this study is to explore the lived experiences of taxpayers regarding justice within the Iranian tax system. Given the importance of tax justice in enhancing voluntary compliance and reducing tax avoidance behaviors, gaining a deeper understanding of taxpayers’ narratives and perceptions can provide new insights for reforming tax policies. This study was conducted using a qualitative design and the grounded theory approach. Data were collected through semi-structured interviews with 15 taxpayers and tax experts and analyzed through open, axial, and selective coding in three stages. The results indicated that taxpayers’ lived experiences of tax justice can be explained through four main dimensions: distributive justice (perceived equity in tax burden), procedural justice (manner of law enforcement), informational justice (transparency in resource use and dissemination of information), and interactional justice (behavior of tax officers). The findings suggest that negative perceptions of justice in any of these dimensions contribute to a decline in institutional trust, the weakening of positive social norms, and the strengthening of tax avoidance behaviors. By highlighting taxpayers’ viewpoints, this study emphasizes the necessity of revising tax system policies and implementation mechanisms with a focus on justice.